Fistula gastrocólica - Henriques,Alexandre Cruz (1999)
A case of gastrocolic fistula(GCF) in a patient with duodenal stenosis who had previously undergone gastroenteric anastomosis is reported. The patient went through hemigastrectomy, partial colectomy and segmental enterectomy with bloc resection. Reconstruction was carried out through Billroth II gastrojejunostomy, jejunojejunostomy and end-to-end anastomosis of the colon. The patient had good post-operative evolution and was discharged from hospital seven days after surgery. GCF should be suspected in patients presenting weight loss, diarrhea and fecal vomiting, mainly with history of peptic ulcer surgery, gastric or colonic malignancy and use of steroidal and nonsteroidal antiinflamatory drugs. Barium enema is the choice test for diagnosis, however, the benign or malignant nature of the lesion should always be evaluated through high digestive endoscopy. Clinical treatment with oral H2-antagonists and discontinuing ulcerogenic medications might be indicated in some cases; surgical treatment is indicated in cases of malignant disease and might be indicated in cases of peptic disease as it treats GCF and also the baseline disease. Some advise upwards colostomy at first. The most used technique is bloc resection, including the fistulous tract, hemigastrectomy and partial colectomy. Gastrectomy, fistulous tract excision and colon suturing may be performed in some cases. The mortality rate is related to metabolic disorders and the recurrence with the use of antiinflammatory drugs.